Analysis of Needs Seawater Purification Devices by Utilising Solars Panels a Physics Learning Media - Ernidawati, Ernidawati; Ulfa, Zulia; Irianti, Mitri; Ma’aruf, Zuhdi; Adh Dhuha, Nur; Akbar, Rayatul (Journal of Educational Sciences, 2025)
This study aims to analyze the needs seawater purification devices by utilising solars panels as a medium for learning physics, the research method used is descriptive with a survey approach, involving 23 teachers and 73 students in junior high and senior high schools in Riau Province. The survey results showed that most students felt that learning physics was difficult to understand, especially in renewable energy materials. The experimental method is the main choice in learning physics, but the limitations of experimental tools, include seawater purification devices by utilising solars panels, inhibits hands-on learning. This tool is not only relevant to support contextual physics learning but also provides insight into the use of renewable energy. This tool helps students understand the concept of physics, the use of this seawater purifier also provides an opportunity to teach students about very relevant environmental issues, such as the scarcity of clean water. The results of the study indicate that the provision of this tool is very necessary to improve students' understanding of physics concepts in a concrete and applicable manner.